IMPLEMENTATION OF DAKWAH IN CAMPUS - Adnan, Mohammad (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2022)
Campus Da'wah is the implementation of Ilallah Da'wah within the scope of Higher Education, intended to call academics to the Islamic path by utilizing various formal/informal facilities on campus. Campus da'wah is also a tiny part of the long path of Islamic da'wah, which is considered to have significant value. The sociological aspect of the da'wah strategy is one of the principles that must be considered in carrying out the da'wah strategy, which addresses issues related to the situation and conditions of the da'wah target. This article uses qualitative methods and makes library research and observation of existing campus da'wah institutions the primary source of research. This article try to find out how to know and implement da'wah on campus. LDK as a means of inter-campus da'wah regeneration ties the brotherhood among fellow Muslims in the campus environment. Seeing the many benefits obtained when the implementation of da'wah is implemented in the campus environment, it would be nice for da'wah activities in the campus environment to be reactivated.